Gold market and selected Nordic stock markets: Granger causality - Mamcarz, Katarzyna (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The turbulence in financial markets, especially stocks, makes investors seek safer ways of capital allocation. Gold exhibiting a low or negative correlation with stocks can constitute an alternative form of investment for them. The price volatility of aforementioned assets has impact on investors’ decisions. That is why the assessment of interrelations between stock and gold returns is important. The direction of causality between the analysed variables is reflected by the fact that investors tend to transfer their funds from gold markets to more profitable markets, or return to gold markets. The research focuses on linkages between gold-stock markets of selected Nordic countries which in comparison with countries classified as key producers and consumers of gold were not under investigation so far. There is therefore a research gap in empirical research. Aim: The aim of this paper is to investigate the causal relationship between the rates of return on stock markets in three Nordic countries, represented by their respective indices — OMXH25 (Finland: the Helsinki Stock Exchange Index), OMXS30 (Sweden: the Stockholm Stock Exchange Index) and OSEAX (Norway: the Oslo Børs All Share Index) — and the returns from investment in gold. The VAR model was applied in the analysis to perform a Granger non-causality linear test, along with decomposition of variance and the impulse response function. The study covered the period between September 2001 and October 2020. Results: The study showed no causality between the analysed rates of return, except in Norway, where the gold market was found to have an impact on the stock market, assuming a statistical significance of 0.14. In the other two countries, changes in gold prices did not affect stock prices, and vice versa.